2019
DOI: 10.1101/664003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transdiagnostic Phenotyping Reveals a Host of Metacognitive Deficits Implicated in Compulsivity

Abstract: Recent work suggests that obsessive-compulsive disorder (OCD) patients have a breakdown in the relationship between explicit beliefs (i.e. confidence about states) and updates to behaviour. The precise computations underlying this disconnection are unclear because casecontrol and transdiagnostic studies yield conflicting results. Here, a large general population sample (N = 437) completed a predictive inference task previously studied in the context of OCD. We tested if confidence, and its relationship to acti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
42
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 42 publications
(75 reference statements)
10
42
2
Order By: Relevance
“…Hypermentalizing is also a possible explanation for the findings of [ 59 ], where similar modeling as in the present study showed that healthy participants at the high end of the paranoia spectrum used similar weighting of social information irrespective of whether incorrect advice was framed to be intentional or not, while low-paranoia participants reduced their social weighting when negative advice was cued to be intentional. Furthermore, a study of healthy participants by our group [ 29 ] found that stronger weighting of social over non-social predictions during decision-making was associated with increased activity in the putamen and anterior insula.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Hypermentalizing is also a possible explanation for the findings of [ 59 ], where similar modeling as in the present study showed that healthy participants at the high end of the paranoia spectrum used similar weighting of social information irrespective of whether incorrect advice was framed to be intentional or not, while low-paranoia participants reduced their social weighting when negative advice was cued to be intentional. Furthermore, a study of healthy participants by our group [ 29 ] found that stronger weighting of social over non-social predictions during decision-making was associated with increased activity in the putamen and anterior insula.…”
Section: Discussionsupporting
confidence: 85%
“…In addition to looking for learning and decision-making differences between the different diagnostic groups that were defined by traditional ICD-10 criteria, we adopted a transdiagnostic perspective to investigate the relation between computational mechanisms of social learning and decision-making with ACIPS, a self-report measure of social anhedonia. Previous studies have adopted such a dimensional approach in the general population and found that patterns in aversive learning mapped onto distinct symptoms of depression, social anxiety, and compulsivity [ 48 , 59 , 60 ]. We, however, could not find any transdiagnostic association of social anhedonia with computational parameters of social learning and decision-making in our data.…”
Section: Discussionmentioning
confidence: 99%
“…This was because our sample size had too low a subject-to-variable ratio (N = 192) for de novo factor analysis, as compared to the original study (N = 1413). Prior studies have demonstrated the stability of the factor structure in new data (Rouault et al, 2018;Seow & Gillan, 2020). Consistent with prior work, the resulting dimension scores were moderately intercorrelated (r = 0.33 to 0.42).…”
Section: Self-report Psychiatric Questionnaires Transdiagnostic Dimesupporting
confidence: 76%
“…For example, individuals high in compulsivity exhibit over-confidence in perceptual decision making tasks and may also have some difficulty in knowing when they are right versus wrong (Rouault, Seow, Gillan, & Fleming, 2018). A subsequent investigation of metacognition with respect to reinforcement learning also found that compulsive individuals were over-confident, but also that their confidence did not update appropriately in response to new evidence and did not inform their behaviour as strongly as those low in compulsivity (Seow & Gillan, 2020). Although not studied in the context of model-based planning specifically, these metacognitive findings suggest the possibility that in compulsivity, model-based planning failures may stem from fundamental issues in acquiring and maintaining an accurate internal model of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that this method can reveal associations that are hidden by categorical disorder groupings. For example, anxious-depression is linked to reduced confidence, while individuals high on the spectrum of compulsivity have elevated confidence (Rouault et al, 2018;Seow and Gillan, 2019). This finding might explain why group level effects in OCD (where patients have high levels of both compulsivity and anxious-depression) have not revealed confidence abnormalities (Hauser et al, 2017;Vaghi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%